2023
DOI: 10.3390/jmse11061212
|View full text |Cite
|
Sign up to set email alerts
|

First Data on the Age and Growth of Schmidt’s cod Lepidion schmidti (Moridae) from Waters of the Emperor Seamounts (Northwestern Pacific)

Abstract: This study presents the first data of growth and age of Schmidt’s cod Lepidion schmidti, a rare and poorly studied member of the Moridae family (Gadiformes, Teleostei). The research was focused on the Emperor Seamounts area with the aim of investigating the age, growth rates, and longevity of this species. The analysis involved examining annual growth increments on sagittal otoliths. Data were taken from longline catches in 2014 and 2016, resulting in the collection of 140 individuals and the use of 70 otolith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…Our results and previous research have suggested possible seasonal movements of P. cynodon, its congener P. japonicus, and its relative Antimora rostrata [8,70], which may also contribute to variations in sex composition. The absence of males among larger specimens of P. cynodon has also been observed for other morids from the North Pacific, e.g., P. japonicus, Antimora microlepis, and Lepidion schmidti [8,47,49].…”
Section: Sex Ratiosupporting
confidence: 62%
See 3 more Smart Citations
“…Our results and previous research have suggested possible seasonal movements of P. cynodon, its congener P. japonicus, and its relative Antimora rostrata [8,70], which may also contribute to variations in sex composition. The absence of males among larger specimens of P. cynodon has also been observed for other morids from the North Pacific, e.g., P. japonicus, Antimora microlepis, and Lepidion schmidti [8,47,49].…”
Section: Sex Ratiosupporting
confidence: 62%
“…A widely employed method for estimating the age of fish using otoliths, which has demonstrated success in demersal (including deep-water) species inhabiting the waters along the west coast of the USA and Canada [40], is the "break and burn" technique. This method has also proven effective in studying the age of some morid species [41][42][43][44][45][46][47][48][49].…”
Section: Analysis Of Biological Datamentioning
confidence: 99%
See 2 more Smart Citations